Whole-Brain Monosynaptic Afferent Inputs to Basal Forebrain Cholinergic System - Hu, Rongfeng; Jin, Sen; He, Xiaobin; Xu, Fuqiang; Hu, Ji (Frontiers in Neuroanatomy, 2016)
The basal forebrain cholinergic system (BFCS) robustly modulates many important behaviors, such as arousal, attention, learning and memory, through heavy projections to cortex and hippocampus. However, the presynaptic partners governing BFCS activity still remain poorly understood. Here, we utilized a recently developed rabies virus-based cell-type-specific retrograde tracing system to map the whole-brain afferent inputs of the BFCS. We found that the BFCS receives inputs from multiple cortical areas, such as orbital frontal cortex, motor cortex, and insular cortex, and that the BFCS also receives dense inputs from several subcortical nuclei related to motivation and stress, including lateral septum (LS), central amygdala (CeA), paraventricular nucleus of hypothalamus (PVH), dorsal raphe (DRN) and parabrachial nucleus (PBN). Interestingly, we found that the BFCS receives inputs from the olfactory areas and the entorhinal-hippocampal system. These results greatly expand our knowledge about the connectivity of the mouse BFCS and provided important preliminary indications for future exploration of circuit function.